An international collaborative evaluation of central serous chorioretinopathy: different therapeutic approaches and review of literature. The European Vitreoretinal Society central serous chorioretinopathy study. Issue 5 (6th December 2019) - Romano, Mario R; Parolini, Barbara; Allegrini, Davide; Michalewska, Zofia; Adelman, Ron; Bonovas, Stefanos; Bopp, Silvia; ,
Abstract: Purpose: To study and compare the efficacy of different therapeutic options for the treatment of central serous chorioretinopathy (CSCR). Methods: This is a nonrandomized, international multicentre study on 1719 patients (1861 eyes) diagnosed with CSCR, from 63 centres (24 countries). Reported data included different methods of treatment and both results of diagnostic examinations [fluorescein angiography and/or optical coherent tomography (OCT)] and best‐corrected visual acuity (BCVA) before and after therapy. The duration of observation had a mean of 11 months but was extended in a minority of cases up to 7 years. The aim of this study is to evaluate the efficacy of the different therapeutic options of CSCR in terms of both visual (BCVA) and anatomic (OCT) improvement. Results: One thousand seven hundred nineteen patients (1861 eyes) diagnosed with CSCR were included. Treatments performed were nonsteroidal anti‐inflammatory eye drops, laser photocoagulation, micropulse diode laser photocoagulation, photodynamic therapy (PDT; Standard PDT, Reduced‐dose PDT, Reduced‐fluence PDT), intravitreal (IVT) antivascular endothelial growth factor injection (VEGF), observation and other treatments. The list of the OTHERS included both combinations of the main proposed treatments or a variety of other treatments such as eplerenone, spironolactone, acetazolamide, beta‐blockers, anti‐anxiety drugs, aspirin, folic acid, methotrexate, statins, vitis vinifera extract medication and pars plana vitrectomy. The majority of the patients were men with a prevalence of 77%. The odds ratio (OR) showed a partial or complete resolution of fluid on OCT with any treatment as compared with observation. In univariate analysis, the anatomical result (improvement in subretinal fluid using OCT at 1 month) was favoured by age <60 years (p < 0.005), no previous observation (p < 0.0002), duration less than 3 months (p < 0.0001), absence of CSCR in the fellow eye (p = 0.04), leakage outside of the arcade (p = 0.05) and fluid height >500 μ m (p = 0.03). The OR for obtaining partial or complete resolution showed that anti‐VEGF and eyedrops were not statistically significant; whereas PDT (8.5), thermal laser (11.3) and micropulse laser (8.9) lead to better anatomical results with less variability. In univariate analysis, the functional result at 1 month was favoured by first episode (p = 0.04), height of subretinal fluid >500 μ m (p < 0.0001) and short duration of observation (p = 0.02). Finally, there was no statistically significant difference among the treatments at 12 months. Conclusion: Spontaneous resolution has been described in a high percentage of patients. Laser (micropulse and thermal) and PDT seem to lead to significant early anatomical improvement; however, there is little change beyond the first month of treatment. The real visual benefit needs further clarification.